2017
DOI: 10.1055/s-0042-122781
|View full text |Cite
|
Sign up to set email alerts
|

l-Lysine Acts as a Serotonin Type 4 Receptor Antagonist to Counteract In Vitro and In Vivo the Stimulatory Effect of Serotonergic Agents on Aldosterone Secretion in Man

Abstract: In the normal human adrenal gland, serotonin (5-HT) stimulates aldosterone secretion through the 5-HT receptor (5-HT4R). However, the physiological role of the serotonergic control of adrenocortical function is not known. In the present study, we have investigated the ability of l-Lysine, which has been shown to act as a 5-HT receptor antagonist, to counteract in vitro and in vivo the stimulatory effect of 5-HT4R agonists on aldosterone production. l-Lysine was found to inhibit aldosterone production induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…HTR4 is serotonin receptor subtype known to be expressed in the adrenal gland according to human tissue specific expression analysis using RNA-seq and proteomics (Fagerberg et al, 2014). Importantly, HTR4 is up-regulated in APAs and serotonin increases aldosterone secretion in vivo and in vitro (Duparc et al, 2017, Ye et al, 2007, Zwermann et al, 2009. Duparc et al reported that serotonin secreted from mast cells stimulates aldosterone production through paracrine regulation in APAs (Duparc et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…HTR4 is serotonin receptor subtype known to be expressed in the adrenal gland according to human tissue specific expression analysis using RNA-seq and proteomics (Fagerberg et al, 2014). Importantly, HTR4 is up-regulated in APAs and serotonin increases aldosterone secretion in vivo and in vitro (Duparc et al, 2017, Ye et al, 2007, Zwermann et al, 2009. Duparc et al reported that serotonin secreted from mast cells stimulates aldosterone production through paracrine regulation in APAs (Duparc et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We have tried to overcome this difficulty by using l-lysine, which acts as a partial 5-HT4 receptor antagonist [63]. We found that diet enriched in this amino acid (5-8 g/ day) did not modify plasma aldosterone levels in healthy subjects in supine and upright positions, or under low sodium diet [64]. The lack of effect of l-lysine on aldosterone production could be ascribed to the low efficiency of the amino acid to antagonize activation of 5-HT4 receptor.…”
Section: Serotonin Secreted By Mast Cells Stimulates Aldosterone Syntmentioning
confidence: 99%
“…The lack of effect of l-lysine on aldosterone production could be ascribed to the low efficiency of the amino acid to antagonize activation of 5-HT4 receptor. Indeed, food supplementation with l-lysine only weakly reduced the plasma aldosterone increase induced by administration of the 5-HT4 receptor agonist metoclopramide [64]. Development of other potent 5-HT4 receptor antagonists which can be administered in humans is therefore required to explore the contribution of 5-HT in the paracrine control of the mineralocorticoid production by mast cells.…”
Section: Serotonin Secreted By Mast Cells Stimulates Aldosterone Syntmentioning
confidence: 99%
“…Besides, the other three DEGs, PCP4, HTR4 and VDR also have been reported to be involved in the occurrence and development of APA [11][12][13] , and among them, the upregulated expression of HTR4 was veri ed by the qPCR in this study. HTR4 is a serotonin receptor subtype known to be expressed in adrenal gland, and serotonin acted on the receptor can increase aldosterone secretion in vivo and in vitro [14][15][16] . In addition, several other DEGs that might be related to calcium signaling pathway and aldosterone secretion, but so far, they have not been reported to participate in the progression of APAs, such as ATP2A3, CLCN5 and AQP2.…”
Section: Discussionmentioning
confidence: 99%